James Merrill : postmodern magus : myth and poetics - Smith, Evans Lansing, 1950- (UPCC book collections on Project MUSE., 2008)
In this meticulously researched, carefully argued work, Evans Lansing Smith argues that the nekyia, the circular Homeric narrative describing the descent into the underworld and reemergence in the same or similar place, confers shape and significance upon the entirety of James Merrill's poetry. Smith illustrates how pervasive this myth is in Merrill's work, not just in The Changing Light at Sandover, where it naturally serves as the central premise of the entire trilogy, but in all of the poet's books, before and after that central text.